Designing Process Diagrams – A Framework for Making Design Choices When Visualizing Process Mining Outputs - Sirgmets, Marit; Milani, Fredrik; Nolte, Alexander; Pungas, Taivo (On the Move to Meaningful Internet Systems. OTM 2018 Conferences, 2018)
Modern information systems can log the executions of the business processes it supports. Such event logs contain useful information on the performance and health of business processes. Event logs can be used in process analysis with the aid of process mining tools. Process mining tools use various diagrams to visualize the output of analysis made. Such diagrams support the visual exploration of the event logs, facilitating process analysis, and usefulness of process mining tools. However, designing such diagrams is not an easy task. Oftentimes neither the developer nor the end-user know how to visualize the outputs created by process mining algorithms, nor do they know where the interesting information is hidden. Designing diagrams for process mining tools require taking design decisions that, on the one hand allow flexible exploration, and on the other hand, are simple and intuitive. In this paper, we investigate how existing process mining outputs are visualized and their underlying design rationale. Our analysis show that process diagrams, the most common type of diagrams used, are designed with next to no guidance from data visualization principles. Based on our findings, we propose a framework to support developers when designing visualization for process mining outputs. The framework is based on data visualization theory and practices within process mining visualization. The effectiveness and usability of the framework is tested in a case study.